The use of random amplified polymorphic dna (RAPD) analysis to determine the genomic heterogeneity among the fungi isolated from agarwood stem - Lim, Wei Yong (Universiti Malaysia Sarawak, (UNIMAS), 2015)
A study was carried out to determine the genomic heterogeneity among fungi isolated from agarwood stem. A total of 17 fungus isolates with 13 unique species was obtained from the Virology Laboratory Unimas which made up of Trichoderma spirale, Trichoderma hamatum, Trichoderma hazianum, Hypocrea lixii, Aspergillus niger, Aspergillus flavus, Aspergillus /ubingensis, Curvularia ajJinis, Grammothele fuligo, Fusarium solani, Lasiodiplodia theobromae, Wllitjordia scopulosa, and Penicillium citrinum. The stock cultures have been revived on the freshly prepared nutrient media potato dextrose agar (PDA) and molecular identification of genetic variability was performed by using the random amplified polymorphic DNA (RAPD) technology. The RAPD-PCR fingerprint obtained by using primer OPA-14 outstood the primer (GTG)s with comparatively high level of polymorphic DNA markers. Gel electrophoresis process was also optimized to which better band patterns in terms of quality and quantity was observed. The resulting band patterns were calculated for their' band scores from which the phylogenetic tree was constructed. From the phylogenetic tree, four fungi namely Trichoderma hamatum, Trichoderma hazianum, Hypocrea lixii, and Aspergillus niger have showed genomic heterogeneity.